(untitled) (Research, Society and Development, 2020)
The mice are widely used in experimental research involving in vivo laboratory tests. It presents small size, easy handling, short reproductive period and easy domestic, which are characteristics that make it a good model, in addition to excellent compatibility with the human genome. The maintenance vivarium adopts different methods of reproduction, often using stranding systems at random, without making a technical analysis of reproductive efficiency. Thus, the present study aims to analyze the reproduction rates of BALB/c mice in different mating systems in the vivarium. Were used 28 BALBm̧ice, 10 males and 18 females distributed among 03 different systems: permanent monogamous, permanent polygamous and temporary polygamous. Three generations were observed for each type of mating in the vivarium of the University Center of Anápolis, UniEvangélica. The permanent monogamous system was the most efficient in the number of pups used, both in birth rate and in weaning. The second generation showed better reproductive efficiency in all systems, in which animals reached greater sexual maturity.